In vivo study of cardioprotective effect of bay leaf (Syzygium polyanthum) extract - Ikhtiari, Refi; Sari, Laura Kartika; Nasution, Ali Napiah; Ginting, Chrismis Novalinda; Handoko, Erwin; Lister, I Nyoman Ehrich (Universitas Muhammadiyah Purwokerto, 2022)
Background: The excessive use of chemotherapy drugs such as doxorubicin might induce cardiovascular diseases. Heart-specific biomarker enzymes such as LDH and BNP indicated the early signs of cardiotoxicity. However, there is no report on the effect of bay leaf on LDH and BNP nor its bioactive compounds and histopathology analysis.Objective: This study aims to determine the cardioprotective effect of Ethanol Extract of Bay Leaf (EEBL) based on phytochemical analysis, LDH and BNP levels, and cardiac histology of rats administered with doxorubicin.Methods: About 24 Wistar rats were divided into six groups treated with 100 mg/kg BW, 300 mg/kg BW, and 500 mg/kg BW of EEBL with CMC-Na 0.5 %, vitamin E, and doxorubicin. Preconditioning was 14 days, followed by 21 days of intraperitoneal administration. LDH and BNP parameters were measured on days 1st, 7th, 14th, and 20th. Histology analysis was conducted on day 21st.Results: Dark green EEBL showed sufficient physical quality and properties for practical application in pharmacy. EEBL has significantly affected LDH, BNP, and cardio recovery dose-dependent. The most effective doses were observed at 500 mg/kg BW, and its performance is not statistically different from those of the commercial vitamin E. The histopathological images revealed significant improvements in interstitial edema, wavy fibers, hemorrhage, intracellular vacuole, and inflammatory cell infiltration. Here we report six bioactive compounds obtained from EEBL have cardioprotective effects; Neophytadiene, squalane, phytol, methyl palmitate, stigmasterol, and 9,12-Octadecanoic acid methyl ester.Conclusion: This study has shown the promising potential of bay leaf extract as a cardioprotector with sufficient quality pharmacological standards.